Speech By Kol. Prof. Dato’ Dr. Kamarudin Hussin, Universiti Malaysia Perlis (UniMAP) Vice Chancellor, at Certificate Ceremony For Agilent – UniMAP Development Program (AUDP) - Kamarudin Hussin, Kol. Prof. Dato’ Dr. (2009)
Ceremony at Agilent Technologies (M) Sdn.Bhd, Penang